PENINGKATAN KEMAMPUAN GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN PADA PEMBELAJARAN TEMATIK MELALUI TEKNIK SUVERVISI KUNJUNGAN KELAS PADA GURU-GURU SMP NEGERI 9 SATAP RAMBAH HILIR KABUPATEN ROKAN HULU - A Basri (STKIP ROKANIA, 2021)
The low quality of human resources, especially educators/teachers, is one of the main problems in the world of education. As the fact that happened at SMPN 9 Satap Rambah Hilir, especially the use of media in learning activities based on the results of the supervision of the principal on 12 teachers found data that in the implementation of learning teachers did not use media. The teacher explains more about the material even though the material can be clarified with easily available media, both media available at school and around the school. Of the 12 teachers at SMPN 9 Satap Rambah Hilir only 3 people (25%) have used media in learning activities while 9 people (75%) still do not use media. With these problems, it must be immediately addressed by efforts to increase the ability of supervising teachers with inter-class visits. This research was carried out in two action cycles with 2 meetings in each cycle. In each cycle there are planning, implementation, observation, and reflection activities. The instrument used is an observation sheet. Observation data were analyzed by descriptive qualitative and descriptive quantitative percentage. The results showed an increase in the teacher's ability to use learning media where in cycle 1, meeting 1 was 60% in the sufficient category, increased at meeting 2 to 67% in the good category. In cycle 1I, meeting 1 increased to 75% in the good category and there was an increase at meeting 2 to 85% in the very good category. Implementation of supervision with inter-class visits technique in cycle I meeting 1 was 64% with good category increasing to 76% with good category at meeting 2, In cycle 2 meeting 1 increased again to 81% with very good category and at meeting 2 to 88% with very good category